Gestão de estoques um estudo comparativo da aplicação da ferramenta curva ABC em uma farmácia. - Evangelista, Denir Carvalho (Universidade Federal do Tocantins, 2022)
This article is characterized as a case study carried out in a pharmacy located in the city of Araguaína/TO, where it was observed how the inventory management process was carried out in that organization. In this context, this work aims to optimize the management of pharmaceutical stocks through the use of the ABC curve tool. The collected data were analyzed using the Microsoft Excel tool, first classifying the sample by the total financial volume of sales, in descending order, and then analyzing which drugs comprised each classification level. The ABC classification made it possible to identify, among the drugs, those that bring the most profitability to the company and, with this, the increased responsibility for these items so that they do not miss out, generating risk to the financial balance and causing the withdrawal of its customers. It is concluded that the ABC classification model applied to the inventory management of the pharmacy helps in the control of the stocked quantities, categorizing the most relevant products for management and enabling means to program inventory reduction policies.